Generating Counter-Public Spheres Through Social Media: Two Social Movements in Neoliberalised South Korea - Young Choi, Su; Cho, Younghan (Javnost-The Public, 2017)
This study discusses the dynamics and natures of counter-public spheres configured by people’s engagements in social movements via social media. It focuses on the ways in which the two social movements in South Korea are mobilised both online and offline. Under the extensive neoliberalisation of South Korea, these social movements widely attracted public attention and mobilised mass participation. This study suggests that the distinct dynamics of the social movements contributed to engendering counter-public spheres by associating online and offline spaces for building solidarity and for expressing people’s discontent against mainstream media. It characterises four aspects of counter-public spheres: active disputes and justification; collaboration and networking; affect and mutual empowerment; and a sense of belonging and connectivity. The article concludes that counter-public spheres help stimulate marginalised voices, invoke public deliberations and actions, and intervene in socio-political decision-making.